(untitled) (Bangladesh Medical Journal, 2014)
Chronic active hepatitis (CAH) and chronic persistent hepatitis (CPH), the two histologically distinct forms of viral hepatitis present with variable clinical features. So liver function tests play the key role in diagnosis and prognosis of these disorders. Among the liver function tests, determination of serum aminotransferases: aspartate aminotransferase (AST), alanine aminotransferase (ALT) and AST/ALT ratio are still popularly used. In fact over the transaminase tests no other enzymatic tests have any particular value. In infiltrative disorders there is damage to both mitochondrial and cytoplasmic membranes. Therefore there is a proportionally greater increase in plasma AST activity than ALT. This comparative study was carried out in the department of Biochemistry, Sir Salimullah Medical College, Dhaka from January 2007 to December 2007 to observe the role of aminotransferases and AST/ALT ratio in CAH and CPH. With prefixed inclusion and exclusion criteria a total of 44 age and sex matched subjects were purposively enrolled in the study. Out of them 20 were CAH and 24 were CPH. Serum AST, ALT and total bilirubin were measured and AST/ALT ratio were calculated. Mentioned parameters were compared between groups. Unpaired student’s t-test and chi (x2) square test were done to detect the significant difference between the groups using SPSS version 12.0. Mean age of the study subjects in CAH and CPH group were 32.20 ± 10.65 years (20-50 years) and 32.83 ± 10.68 years (20-49 years) respectively. There was no significant difference regarding age and sex distribution between the groups (p > 0.05). Mean ± SD serum AST was 295.08 ± 153.77 IU/L and 73.38 ± 45.72 IU/L and ALT was 352.44 ± 206.95 IU/L and 121.01 ± 58.77 IU/L in CAH and CPH respectively and both were statistically highly significant (p < 0.01). Mean ± SD of AST / ALT ratio in CAH and CPH were 0.87 ± 0.14 and 0.59 ± 0.14 respectively and was highly significant (p < 0.01). There was no significant difference in serum bilirubin level between the groups (20.78 ± 14.16 ?mol/L vs. 19.25 ± 15.90 ?mol /L) (p > 0.05). DOI: http://dx.doi.org/10.3329/bmj.v41i2.18795 Bangladesh Medical Journal 2012 Vol. 41 No. 2: 17-19